PERAN MANAJER DALAM MENGELOLA KONFLIK ORGANISASI PENGUSAHA TELAAH TERHADAP HUKUM KETENAGAKERJAAN - Bazarah, Jamil (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2019)
The role of managers in an organization is very important because theexistence of managers becomes a doorstop or becomes one of thespearheads of success in organizing. One of the tasks or roles of themajaner is to be able to manage conflicts in the organization he leads sothat each conflict can be resolved properly and no one feelsdisadvantaged. The purpose of this research is to find out how the role ofmanagers in managing employers' organization conflicts.The role of managers in managing conflicts in an organization is veryimportant including: (1) Managers as mediators in solving problems; (2)Managers as consultants to subordinates; (3) Managers as motivators fortheir organizations; (4) Managers have an important role in decisionmaking; (5) A manager is required to be able to master all problems andcan be resolved with deliberation and good thinking before deciding; and(6) A manager is also expected to be a friend as well as a parent in theorganization so that with such circumstances organizational developmentcan be created properly and can realize what is the vision and mission ofthe organization.